"This Is the Story of Why My Military Career Ended Before It Should Have": Premature Separation From Military Service Among U.S. Women Veterans. (May 2015) - Dichter, Melissa E.; True, Gala
Women who serve in the military benefit from unique opportunities but face strains as a minority population and, compared to men, report greater dissatisfaction with their service and have shorter military careers. We interviewed 35 U.S. women veterans about their decisions to enter and leave military service. Premature separation—leaving military service before one plans, expects, or wants to—was a prominent theme and was often precipitated by gender-based experiences, including interpersonal violence, harassment, and caregiving needs. Findings can inform efforts to improve the length and quality of women's military careers and support women during and after service.